2015
DOI: 10.14639/0392-100x-621
|View full text |Cite
|
Sign up to set email alerts
|

Carcinomi associati al papillomavirus umano: conoscenze, ruolo e attitudini dei medici otorinolaringoiatri in tema di prevenzione

Abstract: L’infezione da papillomavirus umano (HPV), in particolare HPV 16, è un riconosciuto fattore causale delle neoplasie orofaringee. L’incidenza delle neoplasie orofaringee è in aumento in diversi paesi europei, inclusa l’Italia, e negli Stai Uniti dove accurati modelli matematici hanno stimato che supererà quella del cancro alla cervice nella prossima decade. Recenti evidenze scientifiche supportano la potenziale efficacia del vaccino anti-HPV nel controllare quella che è stata definita “l’epidemia di neoplasie H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…An Italian survey on HPV among oncologists revealed that most of them were aware of HPV related to cancer, especially oropharyngeal cancer, and had a positive attitude toward HPV vaccination. 31 Another survey in HPV screening and use on US oncologists revealed that only half of the respondents used HPV for screening and even less than 15% used the reports in direct care for oropharyngeal cancers. 32 A study assessing the knowledge, attitudes, and beliefs of head and neck surgeons regarding HPV education and vaccination through a questionnaire based-survey found that majority of the surgeons were aware about HPV and showed positive attitude for HPV education and vaccination to treat HNC efficiently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An Italian survey on HPV among oncologists revealed that most of them were aware of HPV related to cancer, especially oropharyngeal cancer, and had a positive attitude toward HPV vaccination. 31 Another survey in HPV screening and use on US oncologists revealed that only half of the respondents used HPV for screening and even less than 15% used the reports in direct care for oropharyngeal cancers. 32 A study assessing the knowledge, attitudes, and beliefs of head and neck surgeons regarding HPV education and vaccination through a questionnaire based-survey found that majority of the surgeons were aware about HPV and showed positive attitude for HPV education and vaccination to treat HNC efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Human papillomavirus infection is a recognized causal factor associated with HNC, 31 but its prevalence in Chinese population is relatively low. 1 In the latest NCCN guidelines, HPV test is strongly recommended in HNC and specially in oropharyngeal cancers.…”
Section: Discussionmentioning
confidence: 99%